2004
DOI: 10.1080/18811248.2004.9726351
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Microstructural and Microchemical Effects in Irradiation Assisted Stress Corrosion Cracking using Post-irradiation Annealing

Abstract: Post-irradiation annealing (PIA) was conducted in order to clarify the role of microstructural and microchemical effects on irradiation assisted stress corrosion cracking (IASCC) susceptibility in simulated pressurized water reactor (PWR) primary water. Microstructures, hardening, radiation-induced segregation and IASCC susceptibility were examined in cold-worked SUS 316 stainless steels irradiated to 25 dpa in a PWR after annealing at 673-823 K for 1 h. IASCC susceptibility, microstructures and hardening reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…IASCC susceptibility, mechanical properties and microstructures of the as-irradiated tube materials were thoroughly examined in the previous studies. 4,13,14) It was confirmed that the tube materials were susceptible to IASCC at 4 dpa and highly susceptible at 35 dpa and that the microstructure mainly consisted of dislocation loops with a diameter of $12 nm and dense small bubbles with well-developed grain boundary segregation of Cr, Ni, Si, and Mo.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…IASCC susceptibility, mechanical properties and microstructures of the as-irradiated tube materials were thoroughly examined in the previous studies. 4,13,14) It was confirmed that the tube materials were susceptible to IASCC at 4 dpa and highly susceptible at 35 dpa and that the microstructure mainly consisted of dislocation loops with a diameter of $12 nm and dense small bubbles with well-developed grain boundary segregation of Cr, Ni, Si, and Mo.…”
Section: Methodsmentioning
confidence: 82%
“…Ledge formation and microcracking at grain boundaries were reported in deformed irradiated stainless steels, suggesting that localized deformation is related to grain boundary cracking. 4,7) These previous studies showed the deformation characteristics at doses less than several dpa, where the irradiated materials showed no plastic instability. It is well known that the yield strength saturates at doses near 10 dpa in stainless steels irradiated at approximately 300 C. At doses higher than such level, irradiated stainless steels show extremely low uniform elongation and plastic instability.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…GB Cr concentration is a key factor for the passivation behavior and oxide characteristics near GBs. (2) IASCC susceptibility appeared at the yield strength of 500-600 MPa and increased with increasing yield strength in both BWR and PWR water conditions [5,294]. CGRs of irradiated SSs were slightly higher than the linear trend seen between CGR and yield strength in non-irradiated CW SSs [295,296].…”
Section: Factors Controlling Iasccmentioning
confidence: 96%
“…3,4) Recent studies suggested that the localized deformation near grain boundaries plays an important role in intergranular cracking and IASCC. 5,6) The spacing and inclination angle of surface steps to the loading direction (hereinafter termed ''step angle'') are representative parameters for characterizing localized plastic deformation. The angular distribution of step angle has been obtained experimentally in previous studies.…”
Section: Introductionmentioning
confidence: 99%